PROSES BERPIKIR SISWA TUNAGRAHITA RINGAN DALAM MEMAHAMI KONSEP GEOMETRI BERDASARKAN TEORI JEAN PIAGET - Yosepha Patricia Wua Laja; Justin Eduardo Simarmata; Ferdinandus Mone (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Mental retardation certainly has a different thought process from other normal children. Because it is different, there needs to be a study of the thought process with the aim of finding a solution to overcome the problems that are often faced by mentally retarded students in learning mathematics. The purpose of this study was to describe the thought process of mentally retarded students in understanding geometric concepts based on Piaget's theory. The subjects of this study were two mentally retarded students who were in class VI. The stages of the research carried out were carrying out a learning process for three consecutive days to recognize geometry using visual aids then at the end of the activity, mentally retarded students were given evaluation questions in the form of make a match. The results showed that the two mentally retarded students experienced disequilibrium several times until they finally experienced the process of assimilation and accommodation. However, only one student experienced equilibrium who was able to connect flat figures and spatial figures based on the results of their observations. The learning process for mentally retarded students must be repeated until they arrive at an understanding of mathematics.